PENGARUH PERUBAHAN BEBAN BANDUL GOVERNOR TERHADAP RESPON KECEPATAN PADA MESIN DIESEL - Zaenal Abidin; Gatot Santosos; Muki Satya Permana (PROCEEDING STIMA)
The function of governor is to regulate the speed of an engine when there are variation in the load. When the load on an engine increases, its speed decreases, therefore it is necessary to increase the supply of working fluid & vice-versa. Thus, Governor automatically controls the speed under varying load. The centrifugal governors are based on the balancing of centrifugal force on the rotating balls for an equal and opposite radial force, known as the controlling force. It consist of sum balls of equal mass, which are attached to the arms as shown in fig. when the load on the engine increases, the engine and the governor speed decreases. This results in the decrease of centrifugal force on the balls. Hence the ball moves inward & sleeve moves downwards. The downward movement of sleeve operates a throttle valve at the other end of the bell rank lever to increase the supply of working fluid and thus the speed of engine is increased. In this case the extra power output is provided to balance the increased load.When the load on the engine decreases, the engine and governor speed increased, which results in the increase of centrifugal force on the balls. Thus the ball move outwards and sleeve rises upwards. This upward movement of sleeve reduces the supply of the working fluid and hence the speed is decreased. In this case power output is reduced.Keywords: Governor